Fenomena Benda Pusaka di Tanah Mandar: Perspektif Hukum Islam - Syahrul, Muhammad Alwansyah; Laman, Ilham (Universitas Islam Negeri Alauddin Makassar, 2023)
The tradition of washing Keris and Badik heirlooms has been carried out by some Mandar people for generations, but the sacredness of this traditional ritual should not lead people to worship these sacred objects. The main problem in this research is the phenomenon of heirloom objects in the land from an Islamic legal perspective. This research aims to determine the perspective of Islamic law regarding the phenomenon of heirloom objects in Mandar land. The research method used is field research (file research), namely direct observation of the objects to be studied through interviews, observation, and documentation methods as well as describing the facts in the field to obtain accurate and relevant data in local communities or places. who can be asked about this research? The basis for actions or activities such as washing heirlooms such as keris and badik is based on Islamic values ​​that have been conveyed by the ulama and also ways of broadcasting Islamic teachings in the past using cultures carried out by previous people which are still maintained to this day. in Tanah Mandar. The data sources used in this research come from primary and secondary data. The results of this research are the traditions carried out by the Mandar community, namely washing Keris and Badik heirlooms. It is known that this tradition has been carried out from generation to generation, passed down from ancestors, and is still maintained to this day.